Ecological constraint and the evolution of sexual dichromatism in darters. (1st May 2015) - Bossu, Christen M.; Near, Thomas J.
Abstract: It is not known how environmental pressures and sexual selection interact to influence the evolution of extravagant male traits. Sexual and natural selection are often viewed as antagonistic forces shaping the evolution of visual signals, where conspicuousness is favored by sexual selection and crypsis is favored by natural selection. Although typically investigated independently, the interaction between natural and sexual selection remains poorly understood. Here, we investigate whether sexual dichromatism evolves stochastically, independent from, or in concert with habitat use in darters, a species‐rich lineage of North American freshwater fish. We find the evolution of sexual dichromatism is coupled to habitat use in darter species. Comparative analyses reveal that mid‐water darter lineages exhibit a narrow distribution of dichromatism trait space surrounding a low optimum, suggesting a constraint imposed on the evolution of dichromatism, potentially through predator‐mediated selection. Alternatively, the transition to benthic habitats coincides with greater variability in the levels of dichromatism that surround a higher optimum, likely due to relaxation of the predator‐mediated selection and heterogeneous microhabitat dependent selection regimes. These results suggest a complex interaction of sexual selection with potentially two mechanisms of natural selection, predation and sensory drive, that influence the evolution of diverse male nuptial coloration in darters.